2018
DOI: 10.1002/chem.201804709
|View full text |Cite
|
Sign up to set email alerts
|

Lewis Acid‐Mediated One‐Electron Reduction of Nitrous Oxide

Abstract: The one‐electron reduction of nitrous oxide (N2O) was achieved using strong Lewis acids E(C6F5)3 (E=B or Al) in combination with metallocenes. In the case of B(C6F5)3, electron transfer to N2O required a powerful reducing agent such as Cp*2Co (Cp*=pentamethylcyclopentadienyl). In the presence of Al(C6F5)3, on the other hand, the reactions could be performed with weaker reducing agents such as Cp*2Fe or Cp2Fe (Cp=cyclopentadienyl). The Lewis acid‐mediated electron transfer from the metallocene to N2O resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 123 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…To examine whether the radical anions of Lewis acidic boranes are capable of cleaving hydrogen, a solution of 1 in either CD 2 Cl 2 or [D 8 ]THF was chemically reduced using decamethylcobaltocene (Cp* 2 Co, E 0 =−1.94 V vs. Cp 2 Fe 0/+ ), heated in the presence of H 2 , and the reaction periodically monitored using multinuclear NMR spectroscopy (see the Supporting Information for details). Figure a shows the resulting 11 B NMR spectra.…”
Section: Methodsmentioning
confidence: 99%
“…To examine whether the radical anions of Lewis acidic boranes are capable of cleaving hydrogen, a solution of 1 in either CD 2 Cl 2 or [D 8 ]THF was chemically reduced using decamethylcobaltocene (Cp* 2 Co, E 0 =−1.94 V vs. Cp 2 Fe 0/+ ), heated in the presence of H 2 , and the reaction periodically monitored using multinuclear NMR spectroscopy (see the Supporting Information for details). Figure a shows the resulting 11 B NMR spectra.…”
Section: Methodsmentioning
confidence: 99%
“…In past decade, B(C 6 F 5 ) 3 as a classic Lewis acid is utilized for the construction of the frustrated Lewis pairs (FLP) for the activation of small molecules . Radical anions [B(C 6 F 5 ) 3 ] – • and [Al(C 6 F 5 ) 3 ] – • are able to mediate the chemical reduction of O 2 ,, Se, Te, S 8 , R–X–X–R (X = O, S, Te), N 2 O . Al(C 6 F 5 ) 3 demonstrates decent catalytic activity in polymerization of substituted butyrolactones and benzofuran forming high molecular weight polymers with narrow molecular weight distribution.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12] Radical anions [B(C 6 F 5 ) 3 ] -• and [Al(C 6 F 5 ) 3 ] -• are able to mediate the chemical reduction of O 2 , [13,14] Se, Te, S 8 , R-X-X-R (X = O, S, Te), [7] N 2 O. [15] Al(C 6 F 5 ) 3 [16] demonstrates decent catalytic activity in polymerization of substituted butyrolactones [17] and benzofuran [18] forming high molecular weight polymers with narrow molecular weight distribution. It was found that Al(C 6 F 5 ) 3 is the better catalyst than B(C 6 F 5 ) 3 for the polymerization of l-lactide and ε-caprolactone.…”
Section: Introductionmentioning
confidence: 99%
“…This gas is a long‐lived stratospheric ozone‐depleting substance and greenhouse gas with an impact on global warming 300 times larger than that of carbon dioxide (CO 2 ) [4–7] . The capture and decomposition of nitrous oxide have become important areas of research, also with the aim to use N 2 O as oxygen transfer reagent in chemical syntheses (“oxidations”) [8–16] …”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] The capture and decomposition of nitrous oxide have become important areas of research, also with the aim to use N 2 O as oxygen transfer reagent in chemical syntheses ("oxidations"). [8][9][10][11][12][13][14][15][16] Nitrous oxide is thermodynamically unstable and prone to decomposition into N 2 and O 2 with a standard heat of reaction Δ R H°of À 82.1 kJ mol À 1 . [17] Due to its kinetic inertness (E A 246 kJ mol À 1 ), either high temperatures (400 °C) or the use of heterogeneous catalysts are necessary to facilitate its decomposition at lower T. [11,18,19] Activation of nitrous oxide by homogeneous catalysts can be achieved under considerably milder conditions (T < 150 °C), but the poor ligand capability of nitrous oxide poses a fundamental challenge in the development of such catalytic systems.…”
Section: Introductionmentioning
confidence: 99%